Bibliometric and visualization analysis of kidney repair associated with acute kidney injury from 2002 to 2022 - Li, Jun; Gong, Xuezhong (Frontiers in Pharmacology, 2023)
Background: Renal repair is closely related to the prognosis of acute kidney injury (AKI) and has attracted increasing attention in the research field. However, there is a lack of a comprehensive bibliometric analysis in this research area. This study aims at exploring the current status and hotspots of renal repair research in AKI from the perspective of bibliometrics. Methods: Studies published between 2002 and 2022 related to kidney repair after AKI were collected from Web of Science core collection (WoSCC) database. Bibliometric measurement and knowledge graph analysis to predict the latest research trends in the field were performed using bibliometrics software CiteSpace and VOSviewer. Results: The number of documents related to kidney repair after AKI has steadily increased over 20 years. The United States and China contribute more than 60% of documents and are the main drivers of research in this field. Harvard University is the most active academic institution that contributes the most documents. Humphreys BD and Bonventre JV are the most prolific authors and co-cited authors in the field. The American Journal of Physiology-Renal Physiology and Journal of the American Society of Nephrology are the most popular journals in the field with the greatest number of documents. "exosome ", "macrophage polarization", " fibroblast", and " aki-ckd transition " are high-frequency keywords in this field in recent years. Extracellular vesicles (including exosomes), macrophage polarization, cell cycle arrest, hippo pathway, and sox9 are current research hotspots and potential targets in this field. Conclusion: This is the first comprehensive bibliometric study on the knowledge structure and development trend of AKI-related renal repair research in recent years. The results of the study comprehensively summarize and identify research frontiers in AKI-related renal repair.